Atrial-Specific Gene Delivery Using an Adeno-Associated Viral Vector. Issue 2 (18th January 2019) - Ni, Li; Scott, Larry; Campbell, Hannah M.; Pan, Xiaolu; Alsina, Katherina M.; Reynolds, Julia; Philippen, Leonne E.; Hulsurkar, Mohit; Lagor, William R.; Li, Na; Wehrens, Xander H.T.
Abstract : Rationale: : Somatic overexpression in mice using an adeno-associated virus (AAV) as gene transfer vectors has become a valuable tool to analyze the roles of specific genes in cardiac diseases. The lack of atrial-specific AAV vector has been a major obstacle for studies into the pathogenesis of atrial diseases. Moreover, gene therapy studies for atrial fibrillation would benefit from atrial-specific vectors. Atrial natriuretic factor (ANF) promoter drives gene expression specifically in atrial cardiomyocytes. Objective: : To establish the platform of atrial specific in vivo gene delivery by AAV-ANF. Methods and Results: : We constructed AAV vectors based on serotype 9 (AAV9) that are driven by the atrial-specific ANF promoter. Hearts from mice injected with AAV9-ANF-GFP (green fluorescent protein) exhibited strong and atrial-specific GFP expression without notable GFP in ventricular tissue. In contrast, similar vectors containing a cardiac troponin T promoter (AAV9-TNT4-GFP) showed GFP expression in all 4 chambers of the heart, while AAV9 with an enhanced chicken β-actin promoter (AAV-enCB-GFP) caused ubiquitous GFP expression. Next, we used Rosa26 mT/mG (membrane-targeted tandem dimer Tomato/membrane-targeted GFP), a double-fluorescent Cre reporter mouse that expresses membrane-targeted tandem dimer Tomato before Cre-mediated excision, and membrane-targeted GFP after excision. AAV9-ANF-Cre led to highly efficient LoxP recombination in membrane-targeted tandem dimer Tomato/membrane-targeted green fluorescent protein mice with high specificity for the atria. We measured the frequency of transduced cardiomyocytes in atria by detecting Cre-dependent GFP expression from the Rosa26 mT/mG allele. AAV9 dose was positively correlated with the number of GFP-positive atrial cardiomyocytes. Finally, we assessed whether the AAV9-ANF-Cre vector could be used to induce atrial-specific gene knockdown in proof-of-principle experiments using conditional JPH2 (junctophilin-2) knockdown mice. Four weeks after AAV9-ANF-Cre injection, a strong reduction in atrial expression of JPH2 protein was observed. Furthermore, there was evidence for abnormal Ca 2+ handling in atrial myocytes isolated from mice with atrial-restricted JPH2 deficiency. Conclusions: : AAV9-ANF vectors produce efficient, dose-dependent, and atrial-specific gene expression following a single-dose systemic delivery in mice. This vector is a novel reagent for both mechanistic and gene therapy studies on atrial diseases. Abstract : Supplemental Digital Content is available in the text.